Kites For Peace: Educating "Peace" for Children - Imelda Masni Juniaty Sianipar (JURNAL ComunitÃ Servizio : Jurnal Terkait Kegiatan Pengabdian kepada Masyarakat, terkhusus bidang Teknologi, Kewirausahaan dan Sosial Kemasyarakatan, 2025)
Peace is a universal value that should be instilled from an early age, especially in children as they shape their identities and life principles. By understanding the meaning of peace, children can become positive role models in their communities. The Center for Social Justice and Global Responsibility at LPPM UKI organized a community service initiative titled Kites for Peace in RT 008 and RT 007, RW 010, Cawang Subdistrict, East Jakarta. This initiative aimed to teach children that peace is not merely the absence of violence but also encompasses freedom, happiness, and harmony. The method consisted of two main activities: an interactive lecture encouraging children to understand and find peace in their daily lives and a creative kite-painting session as a medium of expression. The results of the initiative revealed three key findings. First, children were able to define peace based on their own experiences, such as enjoying quiet time reading or sharing toys with friends. Second, they identified ways to create harmony in their environment, including listening to their parents and helping friends in need. Third, they creatively expressed their vision of peace through kite designs, incorporating colors and symbols that reflect their hopes for harmony. Keywords: peace education, kites for peace, children, harmony, positive role models